Chad : Poverty Reduction Strategy Paper-Joint Staff Advisory Note on the 2013 Monitoring Report of the National Development Plan 2013-15. (IMF Staff Country Reports; Country Report, 2015)
This Joint Staff Advisory Note discusses progress in implementing Chad's National Development Plan (NDP) in 2013. The NDP was overall satisfactorily implemented in 2013. By end 2013, about two-thirds of strategic indicators and one-half of intermediary indicators retained in the results framework did record progress in line with retained targets. In addition, the contribution of the 2013 national budget to the NDP implementation was close to initial plans, reflecting structural progress in terms of budget execution. The adoption of a robust Results Framework also allowed the authorities to effectively monitor NDP implementation, in terms of inputs, outputs, and outcomes.